2004
DOI: 10.4102/sajpsychiatry.v10i4.122
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Judicial Section 9 Certification in the Free State

Abstract: A direct referral system for referring persons who perpetrate a crime while suffering from a mental illness has evolved between the office of the Director of Public Prosecution (DPP) in the Free State, and the Free State Psychiatric Complex (FSPC) over the years. The efficiency and impact of this direct referral system have never been quantified. This study found that this alternative system is uncomplicated, functions quite effectively with a minimum of inappropriate referrals, and contributes greatly towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Accountability – according to Section 78 (accountability) of the Criminal Procedures Act 51 of 1977 and Amendment 1998 – ‘the ability of the accused to appreciate the wrongfulness of his or her actions and whether he or she can act in accordance with an appreciation of the wrongfulness of his or her actions’. 10 , 11 …”
Section: Research Methods and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Accountability – according to Section 78 (accountability) of the Criminal Procedures Act 51 of 1977 and Amendment 1998 – ‘the ability of the accused to appreciate the wrongfulness of his or her actions and whether he or she can act in accordance with an appreciation of the wrongfulness of his or her actions’. 10 , 11 …”
Section: Research Methods and Designmentioning
confidence: 99%
“…However, if the accused is evaluated as mentally ill, or if there is doubt concerning the accused’s mental state at the time of the offence (accountability or criminal responsibility), the court will order that the accused be observed in a designated psychiatric facility for a period not exceeding 30 days. 10 , 11 Chapter 13 of the Criminal Procedures Act 51 of 1977 10 , 11 contains provisions for this referral, and consists of three sections, Section 77 (trialability), Section 78 (accountability) and Section 79 (psychiatric assessment procedures). On completion of a psychiatric evaluation by psychiatrists or multidisciplinary mental health teams, an accused can either be found accountable for his or her actions, or not accountable as a result of a mental illness or defect.…”
Section: Introductionmentioning
confidence: 99%
“…If, for example, accused are brought for examinations on a day-visit basis for up to 3 days (depending of individual requirements, of course), the reduction in costs to the relevant state departments, namely, health and justice, could be substantial. While current costs are not available, a 30-day forensic mental health observation was estimated to cost about R30,000 several years ago (Meyer, Slabber, van Rensburg, & Nel, 2004). At current rates, the use of a day-visit approach could result in substantial savings in direct costs.…”
Section: Can the S77 And S78 Accused Be Examined As A Day-visitor?mentioning
confidence: 99%
“…5 The process of a 30-day inpatient assessment is labour intensive, time consuming and expensive. 6 , 7 The Department of Health’s turnaround strategy to reduce the long waiting list found that it was legally compatible for psychiatric forensic observations to be conducted by only one psychiatrist in correctional centres, or on an outpatient basis in specific health establishments. 5 As of March 2010, single psychiatrist observations were conducted in the Northern Cape, North West, Limpopo and the Free State provinces, 5 which were helpful in reducing the number of awaiting-trial detainees requiring forensic assessment, as everyone did not require 30-day inpatient assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on such assessments in South Africa, with most assessments being carried out on an inpatient basis, 8 , 9 , 10 those being conducted on a preliminary outpatient basis having taken place in rural, under-resourced settings. 6 , 11 A number of countries have explored the option of outpatient forensic observations, including Israel, where Olmer found that in 65.2% of the court-ordered psychiatric assessments, the assessing psychiatrist felt that there was no need for hospitalisation or inpatient forensic assessment. The author contended that an outpatient unit dedicated to writing these reports could significantly reduce the rates of hospitalisation.…”
Section: Introductionmentioning
confidence: 99%